PENGALAMAN CLASSROOM-CHATBOT TERPADU: SOLUSI ALTERNATIF BAGI PELAJAR ASING DALAM BERBAHASA INGGRIS - ' Dewi Sari Wahyuni, Darmansyah, Fetri Yeni, J (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2020)
Both in traditional and online English as a Foreign Language (EFL) classroom, interactions between teachers and peers are indeed needed to practice the targeted language. However, in classes attended by a big number of mixed ability learners, these interactions can hardly as effective as is expected. Along with limited available time for studying more about the language in the classroom as Foreign Language Learning (FLL), learners rarely use the target language in their day-to-day life or interacting with a native speaker, and this lack completes its complexity. Therefore, the writer argues that integrating chatbot in the classroom as an alternative solution to cope with learners' lack of interactions using English in the classroom and real life. This paper is a position paper in which the writer presents her arguable opinion on why integrating chatbots in EFL learning can be an alternative solution.Keywords : EFL, FLL, Integrated Classroom, Chatbot Experience